Counter-regulation online: Threat biases retrieval of information during Internet search. (September 2015) - Greving, Hannah; Sassenberg, Kai
Highlights: Threat is likely to occur during self-relevant Internet search (e.g., for health). We investigate how threat affects information retrieval during Internet search. Search term generation and information retrieval are positively biased under threat. Abstract: The Internet is one of the main information sources. It is frequently used to gather information in self-relevant domains, such as health. Self-relevant information is likely to be accompanied by certain affective and motivational states. For instance, individuals may be afraid to be seriously ill and, thus, feel threatened. Threat is known to elicit preferential processing of positive information. Therefore, we predicted that under threat more positive search terms are retrieved from memory and more positive information is retrieved from already encoded online information than in a control condition. Two experiments supported this prediction. Thus, information processing during Internet search is positively biased under threat. This positive bias can satisfy coping needs, but can at the same time have a negative impact on subsequent behavior and decisions.